2010
DOI: 10.1080/09084282.2010.525102
|View full text |Cite
|
Sign up to set email alerts
|

The Presence and Predictive Value of Astereognosis and Agraphesthesia in Patients with Alzheimer's Disease

Abstract: Sensory and motor functions are good markers of neurocognitive decline due to their proximity and hierarchical relationship to high-order processes. The current study investigated if patients with Alzheimer's disease (AD) differed from a healthy control group in two tactile perceptual processes: astereognosis and agraphesthesia. Analyses were also conducted to see if these tactile processes were predictive of higher-order cognitive functioning. Twenty-eight patients with AD (mean age = 75.86) were compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Handedness did not have an effect on the total score and there was no significant difference in the mean score between dominant and non-dominant hands; however, the number of left handed individuals was too low to make a reliable conclusion. Nonetheless, this finding is consistent with a study that showed palm writing on dominant and non-dominant hands had similar means for healthy individuals and for patients with Alzheimer's disease [15].…”
Section: Discussionsupporting
confidence: 91%
“…Handedness did not have an effect on the total score and there was no significant difference in the mean score between dominant and non-dominant hands; however, the number of left handed individuals was too low to make a reliable conclusion. Nonetheless, this finding is consistent with a study that showed palm writing on dominant and non-dominant hands had similar means for healthy individuals and for patients with Alzheimer's disease [15].…”
Section: Discussionsupporting
confidence: 91%